High Surface Area ZnO-Nanorods Catalyze the Clean Thermal Methane Oxidation to CO2 - Tanika Kessaratikoon; Sawarin Saengsaen; Silvano Del Gobbo; Valerio D’Elia; Tawan Sooknoi (Catalysts, 2022)
ZnO nanostructures were synthesized by a combination of non-aqueous and aqueous sol-gel techniques to obtain morphologically different ZnO nanostructures, nanorods, and nanopyramids, featuring oxygen vacancies-rich exposed lattice faces and exhibiting different catalytic properties and activity. In particular, ZnO nanorods with high surface area (36 m2/g) were obtained through a rapid, scalable, and convenient procedure. The materials were tested for complete methane oxidation as an important benchmark reaction that is sensitive to surface area and to the availability of oxygen vacancies. Simple ZnO nanorods derived from nanosized quantum dots showed the best catalytic performance that compared well to that of several literature-reported perovskites, mixed metal oxides, and single-metal oxides in terms of T50 (576 °C) and T90 (659 °C) temperatures. Such a result was attributed to their high surface-to-volume ratio enhancing the availability of catalytically active sites such as oxygen vacancies whose abundance further increased following catalytic application at high temperatures. The latter effect allowed us to maintain a nearly stable catalytic performance with over 90% conversion for 12 h at 700 °C despite sintering. This research shows that ZnO-based nanomaterials with a high surface area are viable alternatives to oxides of commonly applied (but of potentially limited availability) transition metals (La, Mn, Co, Ni) for the complete combustion of methane when working at moderate temperatures (600–700 °C).
Keywords: Catalytic Processes in Materials Science; ZnO doping and properties; Catalysis and Oxidation Reactions